Profile of producer and retailer of flower and ornamental plant - Reis, Michele Valquíria dos; Sant’Ana, Gabriela Silva; Paiva, Patricia Duarte de Oliveira; Bonifácio, Francilene de Lourdes; Guimarães, Paulo Henrique Sales (Ornamental Horticulture, 2020)
The importance of segment of flowers and ornamental plants in agribusiness are growing. Researches that analyze the situation of different sector of this segment may contribute to establishing politics and actions to stimulate its development. In order to attend this purpose, the aim of this research was to analyze segments of the flower and ornamental plant production chain, focusing on producers and retailers. For that, two different surveys were applied, composed of direct and indirect questions. The application was performed online, using social media or in person, in the company location or in trend fairs. It was observed that the flower and ornamental plant production is mainly a familiar business. Another important issue is that the springtime consists of a new date for flower and ornamental plant commercialization. The number of retailers has been increasing, and this segment had some improvements as sales of different products and services. The flower and ornamental plant commercialization are still, in the majority, in physical location shops, besides of all the technologies available for online sales.